The changes in the system of oblique cases in Molise Croatian dialect - Peša Matracki, Ivica (Array, 2013)
Similar to the varieties spoken by other linguistic minorities in Italy, the varieties of Croatian spoken in the Molise region have for centuries coexisted with the Romance varieties. There are three bilingual localities in the Molise region (Acquaviva Collecroce, San Felice del Molise and Montemitro) whose inhabitants use their original dialect after living in the Italian-speaking surroundings for five centuries. During its long coexistence with the Romance varieties, the Molise Croatian dialect has undergone numerous changes that have strongly affected its system on various linguistic levels (for instance, the loss of the neuter gender and the loss of some vocative case forms). All Molise Croats are bilingual since early childhood. Many five-year-olds speak Italian as their mother tongue and know only some Molise Croatian words, without knowing grammar and syntax. The linguistic situation is characterised by absolute language contact in which the borrowings from the adstrate and superstrate Romance varieties are so numerous that the Molise Croatian linguistic community is threatened with extinction. In this perspective of language decay we will try to examine the changes of the morphological features of the cases and verb phrase modified by indirect object in an oblique case (genitive, dative and instrumental case). The direct and the indirect object are noun phrases which are a part of a verb phrase, i.e. they are complements required by the thematic structure of the verb. This means that the presence of arguments in a syntactic structure (at the level of logical form) is legitimate only if the arguments are provided with a Case. The arguments not provided with a Case can not receive a ϑ-role. The corpus is compiled from the data gathered from native speakers, literary works written in Molise Croatian dialect and, most of all, from the local paper Riča živa (Parola viva, 2004-2011 issues). The research on the case inflection and on the indirect object will be more exact if we apply typological and interlinguistic comparison which highlights the differences between genetically different linguistic systems. Our analysis will therefore include not only the Molise Croatian dialect, but the local Molise dialects and standard Italian as well. Since the Molise Croatian dialect presents a continuation of the Štokavian variety of Croatian, the analysis will partly rely on Croatian and its Štokavian variety as well. It is well known that the primary function of the genitive case is the specification of a noun or a noun phrase, while the dative case frequently marks the indirect object. The instrumental case indicates the means by which the action is being carried out. On the other hand, the accusative case is a case typically assigned by the verb. However, in Slavic languages and their dialects which preserve the case inflection, the genitive case is preserved and usually used inside the verb phrase as well (for example It. vergognarsi di Xgen ; Cro. sramiti se Xgen ; Štok. sramiti se Xgen ; Mol. Cro. sramiti se do Xgen). From the typological point of view, there are various parameters which we will use in the comparative research of case category, such as: a. a morphologically marked case vs. a morphologically unmarked case ; b. the number of cases functioning as the direct object and the types of verbs which require those cases ; c. the criteria of a specific case assignment, etc. Due to lack of space, we here cite only three types of verbs which assign the oblique cases: 1. It. aver paura del buio-Gen ; Cro. plašiti se mraka-Gen ; Mol. Cro. sa strašit do škura-Gen. 2. It. gridare a tutti-Dat ; Cro. vikati svima-Dat ; Mol. Cro. zaupijat sekolicimi-Dat ; 3. It. salutare con la mano-Instr ; Cro. pozdraviti rukom-Instr ; Mol. Cro. salutat s rukom-Instr. The theoretical approach to the description of the indirect object marked by the oblique cases will be primarily based on the generative grammar (Chomsky 1995, 1998 ; Burzio 2000, Butt 2006). In our discussion we will describe the main changes of the system of inflection of the oblique cases in Molise Croatian (including the role of case markers), and examine their different syntactic and semantic characteristics (for example, the syntactic properties of the verbs which require the indirect object). Special attention will be paid to the causes of the weakening of the inflection system as well as on those factors which, on the other hand, help maintain the strength of the inflection system which, although with forms and structures which greatly differ from those original ones, continues to function in Molise Croatian dialect.